2012
DOI: 10.3945/ajcn.111.022772
|View full text |Cite
|
Sign up to set email alerts
|

Maternal choline intake modulates maternal and fetal biomarkers of choline metabolism in humans

Abstract: These data suggest that an increment of 25 mg choline/d to meet the demands of pregnancy is insufficient and show that a higher maternal choline intake increases the use of choline as a methyl donor in both maternal and fetal compartments. This trial was registered at clinicaltrials.gov as NCT01127022.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
210
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 144 publications
(216 citation statements)
references
References 32 publications
4
210
0
Order By: Relevance
“…In a 12-wk feeding study examining the impact of pregnancy on biomarkers of choline metabolism, we observed alterations in the concentrations of several choline metabolites (primary endpoint variables) in pregnant (compared with nonpregnant) women including plasma depletion of choline-derived methyl donors and elevations in plasma choline (5). By using stable isotope methodology performed after our initial report (5), the current study sought to provide mechanistic insights into the underlying causes of the pregnancy-induced alterations in choline metabolism. Specifically, we measured the isotopic enrichment of choline-related metabolites in the blood and urine (primary endpoint variables) of our study participants who had consumed methyl-d9-choline during the last half of the 12-wk feeding study (5).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In a 12-wk feeding study examining the impact of pregnancy on biomarkers of choline metabolism, we observed alterations in the concentrations of several choline metabolites (primary endpoint variables) in pregnant (compared with nonpregnant) women including plasma depletion of choline-derived methyl donors and elevations in plasma choline (5). By using stable isotope methodology performed after our initial report (5), the current study sought to provide mechanistic insights into the underlying causes of the pregnancy-induced alterations in choline metabolism. Specifically, we measured the isotopic enrichment of choline-related metabolites in the blood and urine (primary endpoint variables) of our study participants who had consumed methyl-d9-choline during the last half of the 12-wk feeding study (5).…”
Section: Introductionmentioning
confidence: 96%
“…By using stable isotope methodology performed after our initial report (5), the current study sought to provide mechanistic insights into the underlying causes of the pregnancy-induced alterations in choline metabolism. Specifically, we measured the isotopic enrichment of choline-related metabolites in the blood and urine (primary endpoint variables) of our study participants who had consumed methyl-d9-choline during the last half of the 12-wk feeding study (5). As shown in Figure 1, methyl-d9-choline is labeled with deuterium on all 3 methyl groups, which enables assessment of the partitioning of choline (d9-choline metabolite) and its methyl groups (d3metabolites) among the various choline-related metabolic pathways (2) as well as evaluations of PC biosynthesis via the PEMT pathway (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Methionine, betaine, choline, glycerophosphocholine, phosphocholine, phosphatidylcholine, sphingomyelin, and lysophosphatidylcholine, in frozen liver extracts, were measured with the use of liquid chromatography-mass spectrometry (36)(37)(38). SAM and SAH, in frozen liver and whole embryo extracts, were determined with the use of liquid chromatography-mass spectrometry (39,40).…”
Section: Female Mthfd1smentioning
confidence: 99%
“…Notably, increased consumption of dietary choline during pregnancy can improve biomarkers of choline metabolism. For example, consumption of 930 versus 480 mg choline/day by third-trimester pregnant women led to higher circulating concentrations of several choline-derived methyl donors and restored choline partitioning between the CDP-choline and betaine pathways (which compete for choline as a substrate) to a nonpregnant state [6,19].…”
Section: Discussionmentioning
confidence: 99%